Isolation and characterization of NIH 3T3 cells expressing polyomavirus small T antigen. - Noda, T (1986)
The polyomavirus small T-antigen gene, together with the polyomavirus promoter, was inserted into a retrovirus vector pGV16 which contains the Moloney sarcoma virus long terminal repeat and neomycin resistance gene driven by the simian virus 40 promoter. This expression vector, pGVST, was packaged into retrovirus particles by transfection of psi 2 cells which harbor packaging-defective murine retrovirus genome. NIH 3T3 cells were infected by this replication-defective retrovirus containing pGVST. Of the 15 G418-resistant cell clones, 8 express small T antigen at various levels as revealed by immunoprecipitation. A cellular protein with an apparent molecular weight of about 32,000 coprecipitates with small T antigen. Immunofluorescent staining shows that small T antigen is mainly present in the nuclei. Morphologically, cells expressing small T antigen are indistinguishable from parental NIH 3T3 cells and have a microfilament pattern similar to that in parental NIH 3T3 cells. Cells expressing small T antigen form a flat monolayer but continue to grow beyond the saturation density observed for parental NIH 3T3 cells and eventually come off the culture plate as a result of overconfluency. There is some correlation between the level of expression of small T antigen and the growth rate of the cells. Small T-antigen-expressing cells form small colonies in soft agar. However, the proportion of cells which form these small colonies is rather small. A clone of these cells tested did not form tumors in nude mice within 3 months after inoculation of 10(6) cells per animal. Thus, present studies establish that the small T antigen of polyomavirus is a second nucleus-localized transforming gene product of the virus (the first one being large T antigen) and by itself has a function which is to stimulate the growth of NIH 3T3 cells beyond their saturation density in monolayer culture.